The uncanniness of ageing - Hayes, Grahame (PINS-Psychology in Society, 2025)
The study of ageing and old age is not a topic that is commonly pursued in psychological and social studies. The general disparagement of the aged seems also to have affected the academy. However, the appearance of Lynne Segal’s Out of time: The pleasures and perils of ageing in 2013, is in part an attempt to contribute to serious scholarship in the neglected area of “Age studies”. Her text is simultaneously a memoir of a life-long feminist activist and intellectual, as well as a meticulous study of ageing. This review article highlights some of the many issues raised by Segal in the lives of old people: the persistently negative views towards old people; the conflict between the generations; the waning of desire in the aged; the uncanniness of ageing, and death; and the importance of relationships, and living actively and imaginatively in old age.